Utilizing English Videos as Listening Instructional Media to Promote EFL Students' Listening Proficiency - Intan Dewi Rakhmawati; Sayit Abdul Karim; Punta Riyadi Suryantara (LP2M IAIN Sultan Amai Gorontalo, 2023)
The delivery of listening instructions proved difficult for students, who also lacked interest in English subjects. One potential solution to improve their listening skills could be the use of effective learning media that engages their interest in the subject matter. The purposes of this study were to investigate students’ listening proficiency and figure out students’ perceptions of utilizing videos as media for learning English listening subjects. A quantitative research design was applied to gather the data required through a test and questionnaire. Furthermore, a test was used to gather data related to students' listening ability, and a questionnaire was used to find out students' perceptions of utilizing videos as sources of learning listening. Respondents in this study were twenty-five students from the eleventh grade of SMK N 1 Pleret, Yogyakarta. The findings of the present study revealed that the total mean score (????̅) of the students' test results was 76,8, which is categorized as a